Strengthening Santri Discipline: The Critical Role of Dormitory Supervisors at Muhammadiyah Boarding School - Abror , Muhammad Buya Al- Madany; Suud, Fitriah M. (Indonesian Journal of Islamic Education Studies (IJIES), 2024)
Moral degradation among Indonesian teenagers is a problem that has not yet been resolved, wildly since this moral degradation has penetrated boarding school institutions, which have good character education. So, this study aims to identify effective methods dormitory ustaz use in shaping student discipline, investigating obstacles and supporters in shaping student discipline at Muhammadiyah Boarding School Yogyakarta. This research uses a qualitative case study method. Sampling was done by purposive sampling. The informants in this study were dormitory ustaz, santri, and parents of santri. The results of this study show some of the efforts of the boarding coach in improving the disciplinary character of students in the era of moral degradation, including building good communication between the boarding ustaz and the parents of the students, conducting intensive communication with the students and supervising the daily routine of the students. The results of this study also show that ustaz's efforts to improve students' disciplinary character impact their morale. They can recommend that dormitory managers design more effective and sustainable coaching programs to instill disciplinary values.